Some Existence Theorems for Nonconvex Variational Inequalities Problems - Narin Petrot (Abstract and Applied Analysis)
By using nonsmooth analysis knowledge, we provide the conditions for existence solutions of the variational inequalities problems in nonconvex setting. We also show that the strongly monotonic assumption of the mapping may not need for the existence of solutions. Consequently, the results presented in this paper can be viewed as an improvement and refinement of some known results from the literature.